Recombinant murine gamma interferon induces enhanced resistance to Listeria monocytogenes infection in neonatal mice. - Chen, Y (1989)
Neonatal mice within 24 h of birth were highly susceptible to intraperitoneal infection with Listeria monocytogenes. The 50% lethal dose of bacterial cells was 6.3 X 10(1) CFU for neonates and 3.2 X 10(6) CFU for adult mice. A single injection of recombinant murine gamma interferon (rMuIFN-gamma) protected neonatal mice from simultaneous challenge with a lethal dose of L. monocytogenes cells. The rMuIFN-gamma effect was dose dependent: protection was consistently observed in mice treated with rMuIFN-gamma at doses of more than 4 X 10(2) U (0.1 microgram of protein) per mouse. Bacterial growth in the spleens and livers of rMuIFN-gamma-treated neonates was significantly suppressed in comparison with that in the nontreated controls. The infected neonatal mice showed acquired antilisterial resistance against secondary intravenous infection after 4 weeks of age, and this resistance was significantly augmented in mice that had been treated with rMuIFN-gamma.